2022
DOI: 10.3390/diagnostics12112789
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Pleural Effusions from COVID-19 Deceased Patients: Enhanced Inflammatory Markers

Abstract: Critically ill COVID-19 patients with pleural effusion experience longer hospitalization, multisystem inflammatory syndrome, and higher rates of mortality. Generally, pleural effusion can serve as a diagnostic value to differentiate cytokine levels. This study aimed to evaluate the pleural effusions of COVID-19 deceased patients for 182 protein markers. Olink® Inflammation and Organ Damage panels were used to determine the level of 184 protein markers, e.g., ADA, BTC, CA12, CAPG, CD40, CDCP1, CXCL9, ENTPD2, Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Flt3L, an ideal adjuvant that functions as a cytokine and a growth factor, can activate DCs and lymphocytes to enhance innate and adaptive immune responses. In pleural effusions from deceased COVID-19 patients, Flt3L was found to be elevated . According to plasma profiling, the circulation level of Flt3L increased in patients with severe COVID-19 infection, which was associated with endothelial injury .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Flt3L, an ideal adjuvant that functions as a cytokine and a growth factor, can activate DCs and lymphocytes to enhance innate and adaptive immune responses. In pleural effusions from deceased COVID-19 patients, Flt3L was found to be elevated . According to plasma profiling, the circulation level of Flt3L increased in patients with severe COVID-19 infection, which was associated with endothelial injury .…”
Section: Discussionmentioning
confidence: 96%
“…In pleural effusions from deceased COVID-19 patients, Flt3L was found to be elevated. 27 According to plasma profiling, the circulation level of Flt3L increased in patients with severe COVID-19 infection, which was associated with endothelial injury. 28 Moreover, Flt3L was found to be correlated with radiological features in bronchial aspirates from critically ill patients with SARS-CoV-2 infection, 29 which contributed to the regulation of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…PTN was also considered to be a potential biomarker for inflammatory ischemic cardiomyopathy with good ICM recognition [40] . In a proteomic analysis of pleural effusion from dead COVID-19 patients, 182 protein biomarkers including PTN were significantly elevate, indicating immune system overstimulation and cytokine storm [41] . These studies suggested that PTN was involved in the development of some cardiovascular diseases, but its underlying mechanisms are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy additional LRIs involved PSAP (PSAP^LRP1) and members of the S100 protein family S100A8 (S100A8^AGER, S100A8^ITGB2) and S100A9 (S100A9^AGER, S100A9^CD68, S100A9^ITGB2), that have been reported to activate macrophages in COVID-19 (Melms et (Amraei et al, 2022). Beyond the mentioned ligand proteins, it is also relevant to mention that the three most frequent receptors involved in the LRIs (Table S1) were CD44, involved in T-cell abundance and fostering of the cytokine storm linked to poor prognosis of COVID-19 patients (Zick, 2022); ITGB1, that associates with the angiotensinconverting enzyme 2 (ACE2) to mediate SARS-CoV-2 entry (Zhang et al, 2022) and regulates ECM remodeling; and LRP1, that is involved in the overproduction of cytokines and chemokines (Zick, 2022) and enriched in those COVID-19 patients that died (Razaghi et al, 2022) or underwent long haul COVID-19 disease (Gu et al, 2023). The NMF factor scores indicating the strength of each factor in each spot are depicted for illustrative examples of VisiumST slide images throughout COVID-19 induced DAD progression and shown in Figure 3C.…”
Section: Spatial Cell-cell Interactions In the Spectrum Of The Diseasementioning
confidence: 99%